The role of accounting information in the rationalization of expenditure policies on higher education to meet the labor market requirements of a field study of the University of Sirte - Ahmed, Shahabuddin Mohamed; Al Maqtese, Taj Alsar ali Ahmed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study carried out to study bridge gap between higher education, and Community service. In addition, to highlight the output of higher education and its importance in fulfilling the requirements of the Libyan labor market, and examine policies to rationalize spending and the extent of its impacts on the quality of education output and suitability to the needs and requirements of the labor market in the future. The study relied on a method of descriptive statistical analysis to analyze the raw data obtained from the questionnaire using a statistical program (SPSS) to get to the results of the study premise and tested through correlation matrix and simple regression analysis The study resulted in the following findings: - - The university, like other public sector units to license its annual set of allocated to finance ongoing activities what you offer these units of accounting information funds. - Spending is not objective judgment on the efficiency due to the limited range of models and methods that are included in the plans in order to meet the requirements of the Libyan labor market. - The quality of accounting information to find a property in decisions making to contribute to the policy of fiscal spending on higher education as reflected positively on the economic return.